UPAYA MENINGKATKAN HASIL BELAJAR SENI BUDAYA DENGAN PENERAPAN MODEL PROJECT BASE LEARNING (PjBL) MENGGUNAKAN MINDMAPPING PADA PESERTA DIDIK KELAS X BDPM 1 SMKN 2 DENPASAR SEMESTER 2 TAHUN 2022/2023 - I Ketut Muada; Nazzala Sophie Yustina (CV. ADIBA AISHA AMIRA, 2023)
This research was structured to improve student learning outcomes in learning Arts and Culture using the Project Based Learning (PjBL) learning model for students in class X BDPM 1 SMKN 2 Denpasar in the 2022/2023 Academic Year. This type of research is Classroom Action Research (CAR). Based on the calculation of the value of learning outcomes, the results of student learning scores have fulfilled the requirements to continue in the next cycle, with an average score of 69.3 in cycle I. While in cycle II it was 73.4 so that the target of successful learning outcomes in cycle II was achieved and the average student learning outcomes have exceeded the Minimum Passing Criteria (KKM), which is 70.0 so that research can be stopped and continued with data analysis. Thus the use of Project Based Learning in the subject of Cultural Arts can increase the learning activity of students in class X BDPM 1 SMKN 2 Denpasar in the 2022/2023 Learning Year.